Synthesis, Characterization and Biological Activities of Some New Hypophosphorous Adducts of Acidhydrazones Derived from 2-[(N-benzoyl)-2,5-dichloroanilido]acetohydrazide - Narayan Sharma, Raj; Sharma, K.P. (Asian Journal of Chemistry, 2011)
A new series of hypophosphorous adducts of acidhydrazones have been synthesized by the reaction of 2-[N-(benzoyl)-2,5-dichloroanilido]acetohydrazide with various carbonyl compounds in 43 to 66 % yield. Newly synthesized compounds have been tested for their antibacterial activity against gram positive bacteria S. albus, S. aureus and gram negative bacteria E. coli and Pseudomonas piosineus. The compound (1, 4, 10, 12, 15) show significant activities and compound (2, 6, 9, 16, 17) show moderate activity. The same compounds were tested for their antifungal activity against Candida albicans, Aspergillus niger and Alternaria alternata at concentration of 30 mg/mL using Savored dextrose agar media. The compound (1, 7, 13, 14, 15) show significant activities and compound (2, 5, 8, 16) have shown moderate activity against Candida albicans and Aspergillus niger. All the other compounds did not show significant activity against the fungi at the concentration used.